An engineered variant of MECR reductase reveals indispensability of long-chain acyl-ACPs for mitochondrial respiration - Tanvir Rahman, Mohammad; Koski, M. Kristian; Panecka-Hofman, Joanna; Schmitz, Werner; Kastaniotis, Alexander J.; Wade, Rebecca C.; Wierenga, Rik K.; Kalervo Hiltunen, J.; Autio, Kaija J. (Nature Communications, 2023)
Mitochondrial fatty acid synthesis (mtFAS) is essential for respiratory function. MtFAS generates the octanoic acid precursor for lipoic acid synthesis, but the role of longer fatty acid products has remained unclear. The structurally well-characterized component of mtFAS, human 2E-enoyl-ACP reductase (MECR) rescues respiratory growth and lipoylation defects of a Saccharomyces cerevisiae Δetr1 strain lacking native mtFAS enoyl reductase. To address the role of longer products of mtFAS, we employed in silico molecular simulations to design a MECR variant with a shortened substrate binding cavity. Our in vitro and in vivo analyses indicate that the MECR G165Q variant allows synthesis of octanoyl groups but not long chain fatty acids, confirming the validity of our computational approach to engineer substrate length specificity. Furthermore, our data imply that restoring lipoylation in mtFAS deficient yeast strains is not sufficient to support respiration and that long chain acyl-ACPs generated by mtFAS are required for mitochondrial function.
Gesehen am 09.08.2023